TI_GERICHTE 17.2018.193 vom 5. März 2020 , Prosciolti dall'imputazione di violazione delle regole dell'arte edilizia - TI Tribunale d'appello (2020)
Prosciolti dall'imputazione di violazione delle regole dell'arte edilizia